A Needs Analysis of EYL Teacher Candidates for Effective Learning at Universitas PGRI Silampari - Oktaviani, Ayu; Yulfi; Troyogo, Agus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This research aimed to find out EYL Teacher Candidates for effective learning at Universitas PGRI Silampari. The significances of this research are as a knowledge for researcher in forming learning methods according to the needs of teachers candidates, to conduct effective EYL class based on teachers candidates’ need and condition, and as a reference and information for the next research. This research used qualitative descriptive method, meanwhile the technique for collecting the data was questionnaire. Techniques for analyzing data were data reduction, data display, and conclusion. Based on the research, the researcher found out that the students’ wants of lecturer: help the students’ micro teaching, designing the syllabus, material development, pronunciation, be wise, discipline, healthy, patient, comfortable, enjoyable, and motivated lecturer. Nonetheless, the students’ wants of using skills in English were understanding exam or homework question or task, making a plan, finding documents using library and internet, evaluating the quality of documents, presenting orally, managing time, dealing with disagreement and conflict in group work, motivating self, using computers and internet, preparing for and taking test or exams, and reducing learning stress. The students’ necessities of the skills are studied in semester 1, 3, and 4. In conclusion, the students’ lacks were difficulty in completing final project, less vocabulary, less confidence, less partner in speaking, and stress of too much assignment. Keywords: EYL, Need Analysis, Teachers Candidates.